The work of the epic narrative style in the Iraqi theatrical text Jalil Al-Qaisi - a model (Journal of the College of Basic Education, 2022)
The follower can urge the epic narrative presence in the Iraqi theatrical text, which works to perpetuate the momentum of the dramatic action within the sequences of the events of the text, as the epic narrative presence carries with it the narrative body and the descriptive expression that gives suspense, anticipation and news, as it makes the narrative of its existence a major center within the components of the elements The Iraqi theatrical text, and therefore the task of the research is to know the work of the epic narration within the components of the Iraqi theatrical text and to define its effectiveness in the production of the dramatic act in the theatrical texts of Jalil al-Qaisi, remove the ambiguity of this narrative presence and understand the reasons for the enrichment between it and the other elements constituting the text and shed light on the feasibility of that interaction in the production of the dramatic act,